Welfare and Environmental Benefits of Electric Vehicle Tax Policies in Developing Countries : Evidence from Colombia - Callejas, Jerónimo; Linn, Joshua; Steinbuks, Jevgenijs (World Bank, Washington, DC, 2022)
Developing countries face a major challenge of decarbonizing their light-duty vehicle fleet and transitioning to the broad use of electric vehicles. However, there is little evidence on which policies can most effectively facilitate that transition in these countries, distinguished by relatively low-income consumers and highly concentrated markets that distort vehicle markups. This paper analyzes existing and proposed policies aiming to reduce emissions from new passenger vehicles in Colombia, which has used preferential sales taxes and import tariffs to stimulate hybrid and electric cars sales. Using highly detailed data on vehicle purchases and attributes, the paper estimates an equilibrium model of Colombia’s market that includes a random-coefficients logit demand structure and endogenizes firms’ markups. Using the model to simulate policies, the analysis finds that Colombia’s sales tax and import tariffs have increased hybrid and electric vehicle market shares by 0.9 to 2.7 percentage points at welfare costs of $40-$48 per ton of carbon dioxide reduction. Potentially taxing carbon dioxide emissions rates of new vehicles would have roughly similar welfare costs. The high welfare costs of these policies arise from preexisting distortions caused by market power, which yields large private welfare costs of shifting from gasoline to hybrid and electric vehicles.